Design and fabrication of an oscillating sieve for studies on black pepper grading in the laboratory - BALACHANDRAN PILLAI G; Sabu M. S; Sivarajan K; Er. Jippu Jacob (Guide) (Tavanur 1992 Department of Farm Power Machinery and Energy)
Design and fabrication of an oscillating sieve for studies on black pepper grading in the laboratory
Design and fabrication of an oscillating sieve for studies on black pepper grading in the laboratory